Bentham and the arts - Julius, Anthony, 1956-; Quinn, Malcolm, 1963-; Schofield, Philip, 1958- (UCL Press, 2020)
Bentham and the Arts considers the sceptical challenge presented by Jeremy Bentham's hedonistic utilitarianism to the existence of the aesthetic. Leading scholars from a variety of disciplines reflect on the implications of Bentham's radical utilitarian approach for our understanding of the history and contemporary nature of art, literature, and aesthetics more generally.